RELEVANSI GAMBAR DAN TUTURAN PADA KOMIK SHIN KOBOCHAN TINJAUAN PRAGMATIK - Idrus Idrus (Puitika, 2017)
This article discusses the relevance between the image and the speech in Japanese. This study is a qualitative research that discusses and explains the relevance between the image and the speech in strip comic. The aims of this research to analyze the relevance between the image and the speech that triggered the formation of story in strip comic. The data of this study are taken from “Shin Kobochan” strip comic by Masashi Ueda volume 28, 29 and 30, published in 2014 by Houbunsha. The theories employed in this study are Sperber and Wilson’s relevance theory, which aims to see the relevance between the speech and the images in the form of humor utterances, Danesi and Peron’s iconicity theory, Pierce’s theory of semiosis process, which aim to interpret the images and Grice’s implicatures theory which aims to reveal the implicit meaning of the utterances. The results show that Images showing the speaker and hearer performing certain activity are required in the process of understanding the whole humor, so that the communicated meaning and the message can be found. Keywords: relevance, image, utterance, icons, and semiosis